2015
DOI: 10.1103/physrevb.92.081111
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Josephson effect in double-layer graphene junctions

Abstract: We show that double-layer graphene (DLG), where an external potential induces a charge imbalance between n-and p-type layers, is a promising candidate to realize an exciton condensate in equilibrium. To prove this phenomenon experimentally, we suggest coupling two DLG systems, separated by a thin insulating barrier, and measuring the excitonic Josephson effect. For this purpose we calculate the ac and dc Josephson currents induced by tunneling excitons and show that the former only occurs when the gate potenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This statement is also in agreement with the recent work in Ref. [66], where it has been shown that the excitonic Josephson current becomes extremely small before the EI state breaks down. A detailed analysis of the role of the CNP point W C = 1.48999γ 0 , for the case of interaction balanced BLGs, is given in Fig.…”
Section: The Normal Quasiparticle Tunnelingsupporting
confidence: 93%
See 1 more Smart Citation
“…This statement is also in agreement with the recent work in Ref. [66], where it has been shown that the excitonic Josephson current becomes extremely small before the EI state breaks down. A detailed analysis of the role of the CNP point W C = 1.48999γ 0 , for the case of interaction balanced BLGs, is given in Fig.…”
Section: The Normal Quasiparticle Tunnelingsupporting
confidence: 93%
“…The excitonic Josephson tunneling effects and thermal transport properties in the electron-hole type double-layer graphene junctions, separated by a dielectric layer, have been recently considered in Refs. [66,67].…”
Section: Introductionmentioning
confidence: 99%
“…Josephson effect is particularly attractive to condensed matter researchers because it serves as the striking manifestation of coherent condensation and the promising candidate for quantum technology. The unrelenting and strong attention has been recently received in opticallyexcited exciton or exciton-polariton cold gases [1][2][3][4][5][6][7] and graphene electron-hole bilayer exciton 8,9 . The quantum Hall bilayer, which is the most practicable one to achieve the exciton condensation , however, remains not studied extensively in the land of Josephson effect to date.…”
Section: Introductionmentioning
confidence: 99%
“…Here we propose that the Josephson effect [10,11] can provide an unambiguous signal of the electron-hole superfluidity. In a Josephson junction, two superfluids are separated by a thin potential barrier, and a phase difference between the superfluids leads to a steady current flow.…”
mentioning
confidence: 99%